Age and Tumor Differentiation-Associated Gene Expression Based Analysis of Non-Familial Prostate Cancers - Sharad, Shashwat; Allemang, Travis C.; Li, Hua; Nousome, Darryl; Ku, Anson Tai; Whitlock, Nichelle C.; Sowalsky, Adam G.; Cullen, Jennifer; Sesterhenn, Isabell A.; McLeod, David G.; Srivastava, Shiv; Dobi, Albert (Frontiers in Oncology, 2021)
Prostate cancer incidence in young men has increased. Patients diagnosed at an earlier age are likely to have aggressive prostate cancer and treatment decisions are continuing to be weighted by patient age and life expectancy. Identification of age-associated gene-expression signatures hold great potential to augment current and future treatment modalities. To investigate age-specific tumor associated gene signatures and their potential biomarkers for disease aggressiveness, this study was designed and stratified into well and poorly differentiated tumor types of young (42-58 years) and old (66-73 years) prostate cancer patients. The differentially expressed genes related to tumor-normal differences between non-familial prostate cancer patients were identified and several genes uniquely associated with the age and tumor differentiation are markedly polarized. Overexpressed genes known to be associated with somatic genomic alterations was predominantly found in young men, such as TMPRESS2-ERG and c-MYC. On the other hand, old men have mostly down-regulated gene expressions indicating the loss of protective genes and reduced cell mediated immunity indicated by decreased HLA-A and HLA-B expression. The normalization for the benign signatures between the age groups indicates a significant age and tumor dependent heterogeneity exists among the patients with a great potential for age-specific and tumor differentiation-based therapeutic stratification of prostate cancer.